Leafspot of Hevea brasiliensis caused by Corynespora cassiicola in the Philippines 1st report - Tangonan, Naomi G.; Pecho, Jasmin A; Butardo, Elaine Genevive G. (2009)
This is the first report of the incidence or occurence of a leafspot or leaf fall disease caused by Corynespora cassiicola (Berk. and Cutr.) Wei affecting rubber (Hevea brasiliensis) in this country. The disease was first observed by the author-researchers in RRIM 600 rubber seedlings and young trees at USMARC nurseries and plantations sometime in October 2008. Standard laboratory procedures were done: fresh specimens of infected rubber leaves collected, thin sections of the infected tissues made, and direct examinations on slide mounts observed under a compound microscope. Morphocultural characteristics of the fungus were noted through microscopy and the fungal growth observed on various culture media. Pathogenecity tests were confirmed by inoculating healthy Hevea seedlings. Identity was confirmed through literatures.
Keywords: Rubber plants -- Diseases and pests; Mindanao studies